Exposure and impact of TV Islamic reality show among Malay community - A. Manaf, Aini Maznina; Wok, Saodah; Ismail, Rizalawati; Abdul Latif, Siti Sakinah (2013)
Islamic TV reality shows are popular among the Muslim community in Malaysia. The most popular one, Imam Muda, has successfully reached its target when the program has been viewed by a large of number of audience and broadcasted for the third season since its inception in 2010. Despite its popularity, there is no effort done to examine the effects of Imam Muda on its viewers. This paper examines the influence Imam Muda reality show in changing the Islamic knowledge, teachings, belief, practices, skills and spirituality of the Malay community in Malaysia. The specific objectives of the study are (a) to find out the level of exposure, perception, attitude, satisfaction of Imam Muda, and the Islamic impact change on the Malay community; (b) to gauge the relationships between exposure, perception, attitude, and satisfaction with the level of Islamic impact change on the Malay community; and (c) to determine the best predictor for the Islamic impact change on the Malay community. This study tests the application of Cultivation Theory (Gerbner, 1972) on Islamic reality show, specifically the Imam Muda program. Attention given to Islamic reality show gradually leads to adoption of Islamic spirituality by the Malay community in total. This study employs a quantitative research design whereby questionnaire was used as the survey research instrument to collect data. From a total of 535 Malays surveyed in Malaysia, 419 respondents watched Imam Muda. The results showed that 57.2% of the Malay community watched Imam Muda for 1-2 hours per sitting and they gave moderate attention to the program. The Malay community has a good perception of Imam Muda, has a positive attitude towards Imam Muda, is satisfied with the program, and thus giving the Malay community some impacts, specifically on their Islamic knowledge, teachings, belief, practices, skills and spirituality. The findings also showed that there is a positive relationship between exposure, perception, attitude and satisfaction with Imam Muda program in relation to Islamic impact change on the Malay community. Although perception, attitude and satisfaction contribute to the Islamic impact change in the Malay community, the best predictor to the Islamic impact change is the satisfaction toward the program. Hence, it can be concluded that Imam Muda program is able to inculcate some Islamic aspects on the Malay community. This indicates that to a certain extent Cultivation Theory holds true for the Imam Muda program, the most popular Islamic reality show in Malaysia.